2020
DOI: 10.1186/s12905-020-01085-4
|View full text |Cite
|
Sign up to set email alerts
|

Is body mass index associated with irregular menstruation: a questionnaire study?

Abstract: Background Irregular menstrual cycles including the length of cycles and menses, and heavy menstrual blood loss are linked to many gynaecological diseases. Obesity has been reported to be associated with irregular menstrual cycles. However, to date, most studies investigating this association are focused on adolescence or university students. Whether this association is also seen in adult women, especially women who had a history of birth has not been fully investigated. Methods Questionnaire data were colle… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 21 publications
3
23
0
Order By: Relevance
“…E. Nelson, E. F. Chukwuma Open Journal of Obstetrics and Gynecology and Amenorrhoea in obese infertility women. This confirms the findings of Yunhui et al [51] and Labban, [52] which reported that BMI is positively associated with Amenorrheoa and Hypogonadism. However, the study observed no correlation between BMI and Hypergonadism and Hypergonadotropic in infertile obese women.…”
Section: Discussionsupporting
confidence: 92%
“…E. Nelson, E. F. Chukwuma Open Journal of Obstetrics and Gynecology and Amenorrhoea in obese infertility women. This confirms the findings of Yunhui et al [51] and Labban, [52] which reported that BMI is positively associated with Amenorrheoa and Hypogonadism. However, the study observed no correlation between BMI and Hypergonadism and Hypergonadotropic in infertile obese women.…”
Section: Discussionsupporting
confidence: 92%
“…These hypotheses warrant further investigation in a causally motivated framework, as what we present here is purely associational. We were able to replicate previously reported associations with own smoking (12, 40) and higher BMI (15, 41) with both menstrual symptoms, guided by methylation markers. We believe that this is the first study to present evidence that that early life experiences such as ACEs and prenatal exposures such as maternal smoking are associated with these conditions.…”
Section: Discussionsupporting
confidence: 76%
“…ALSPAC has repeat measures of the presence of dysmenorrhea and HMB throughout adolescence. In the literature, known causes and risk factors (outside diagnosed gynaecological problems) are scant, with some evidence suggesting smoking (40) and BMI (15, 41) are associated with these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, both extremes of BMI were associated with abnormal periodic blood loss compared to individuals with normal BMI, although the risk of abnormal periodic menstrual bleeding was higher in overweight and obese compared to underweight individuals. In the study by Yunhui Tang, the odds of having heavy menstrual bleeding were less in underweight individuals as compared to those with normal BMI [ 30 ]. Increased menstrual blood loss in obese women is attributed to delayed endometrial repair secondary to a proinflammatory local endometrial environment in obese women [ 31 ].…”
Section: Discussionmentioning
confidence: 99%